Readmissions Within 48 Hours of Discharge: Reasons, Risk Factors, and Potential Improvements. Issue 8 (August 2020) - Grass, Fabian; Crippa, Jacopo; Lovely, Jenna K.; Ansell, James; Behm, Kevin T.; Achilli, Pietro; Hübner, Martin; Kelley, Scott R.; Mathis, Kellie L.; Dozois, Eric J.; Larson, David W.
Abstract : BACKGROUND: Hospital readmission rate is an important quality metric and has been recognized as a key measure of hospital value-based purchasing programs. OBJECTIVE: This study aimed to assess the risk factors for hospital readmission with a focus on potentially preventable early readmissions within 48 hours of discharge. DESIGN: This is a retrospective cohort study. SETTINGS: This study was conducted at a tertiary academic facility with a standardized enhanced recovery pathway. PATIENTS: Consecutive patients undergoing elective major colorectal resections between 2011 and 2016 were included. MAIN OUTCOME MEASURES: Univariable and multivariable risk factors for overall and early (<48 hours) readmissions were identified. Specific surgical and medical reasons for readmission were compared between early and late readmissions. RESULTS: In total, 526 of 4204 patients (12.5%) were readmitted within 30 days of discharge. Independent risk factors were ASA score (≥3; OR, 1.5; 95% CI, 1.1–2), excess perioperative weight gain (OR, 1.7; 95% CI, 1.3–2.3), ileostomy (OR, 1.4; 95% CI, 1–2), and transfusion (OR, 2; 95% CI, 1.4–3), or reoperation (OR, 11.4; 95% CI, 7.4–17.5) during the index stay. No potentially preventable risk factor for early readmission (128 patients, 24.3% of all readmissions, 3% of total cohort) was identified, and index hospital stay of ⩽3 days was not associated with increased readmission (OR, 0.9; 95% CI, 0.7–1.2). Although ileus and small-bowel obstruction (early: 43.8% vs late: 15.5%, p < 0.001) were leading causes for early readmissions, deep infections (3.9% vs 16.3%, p < 0.001) and acute kidney injury (0% vs 5%, p = 0.006) were mainly observed during readmissions after 48 hours. LIMITATIONS: Risk of underreporting due to loss of follow-up and the potential co-occurrence of complications were limitations of this study. CONCLUSIONS: Early hospital readmission was mainly due to ileus or bowel obstruction, whereas late readmissions were related to deep infections and acute kidney injury. A suspicious attitude toward potential ileus-related symptoms before discharge and dedicated education for ostomy patients are important. A short index hospital stay was not associated with increased readmission rates. See Video Abstract at http://links.lww.com/DCR/B237 . REINGRESOS DENTRO DE LAS 48 HORAS POSTERIORES AL ALTA: RAZONES, FACTORES DE RIESGO Y POSIBLES MEJORAS: ANTECEDENTES: La tasa de reingreso hospitalario es una métrica de calidad importante y ha sido reconocida como una medida clave de los programas hospitalarios de compras basadas en el valor. OBJETIVO: Evaluar los factores de riesgo para el reingreso hospitalario con énfasis en reingresos tempranos potencialmente prevenibles dentro de las 48 horas posteriores al alta. DISEÑO: Estudio de cohorte retrospectivo. ESCENARIO: Institución académica terciaria con programa de recuperación mejorada estandarizado. PACIENTES: Pacientes consecutivos sometidos a resecciones colorrectales mayores electivas entre 2011 y 2016. PRINCIPALES MEDIDAS DE RESULTADO: Se identificaron factores de riesgo uni y multivariables para reingresos totales y tempranos (<48 horas). Se compararon razones médicas y quirúrgicas específicas para el reingreso entre reingresos tempranos y tardíos. RESULTADOS: En total, 526/4204 pacientes (12, 5%) fueron readmitidos dentro de los 30 días posteriores al alta. Los factores de riesgo independientes fueron puntuación ASA (≥3, OR 1.5; IC 95% 1.1–2), aumento de peso perioperatorio excesivo (OR 1.7; IC 95% 1.3–2.3), ileostomía (OR 1.4, IC 95%: 1–2) y transfusión (OR 2, IC 95% 1.4–3) o reoperación (OR 11.4; IC 95% 7.4–17.5) durante la estadía índice. No se identificó ningún factor de riesgo potencialmente prevenible para el reingreso temprano (128 pacientes, 24.3% de todos los reingresos, 3% de la cohorte total), y la estadía hospitalaria índice de ⩽ 3 días no se asoció con un aumento en el reingreso (OR 0.9; IC 95% 0.7–1.2) Mientras que el íleo / obstrucción del intestino delgado (temprano: 43.8% vs. tardío: 15.5%, p < 0.001) fueron las principales causas de reingresos tempranos, infecciones profundas (3.9% vs 16.3%, p < 0.001) y lesión renal aguda (0 vs 5%, p = 0.006) se observaron principalmente durante los reingresos después de 48 horas. LIMITACIONES: Riesgo de subregistro debido a la pérdida en el seguimiento, posible co-ocurrencia de complicaciones. CONCLUSIONES: El reingreso hospitalario temprano se debió principalmente a íleo u obstrucción intestinal, mientras que los reingresos tardíos se relacionaron con infecciones profundas y lesión renal aguda. Es importante tener una actitud suspicaz hacia los posibles síntomas relacionados con el íleo antes del alta y una educación específica para los pacientes con ostomía. La estadía hospitalaria índice corta no se asoció con mayores tasas de reingreso. Consulte Video Resumen en http://links.lww.com/DCR/B237 .